Field-laboratory assessment of predatory response of Chilocorus melanophthalmus and Scymnus sp. against Aulacaspis tegalensis (Hemiptera: Diaspididae) infestation on sugarcane (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pramono S. 2025. Field-laboratory assessment of predatory response of Chilocorus melanophthalmus and Scymnus sp. against Aulacaspis tegalensis (Hemiptera: Diaspididae) infestation on sugarcane. Biodiversitas 26: 4057-4064. Sugarcane production in Indonesia is significantly affected by pest infestations, among which the sugarcane scale insect (Aulacaspis tegalensis) is particularly destructive due to its ability to reduce both crop yield and quality. This study aimed to evaluate the potential of natural enemies as biological control agents for A. tegalensis to provide a more sustainable alternative. Field and laboratory experiments were conducted from April 2021 to September 2022 in sugarcane plantations in Central Lampung, Lampung, Indonesia. Field experiments, arranged in a randomized block design, monitored predator-prey interactions and measured predator attack rates on A. tegalensis. Laboratory experiments, using a completely randomized design, evaluated predation at prey densities of 10-320 individuals with two predator species, Chilocorus melanophthalmus and Scymnus spp.. The results showed that C. melanophthalmus and Scymnus spp. had moderate positive correlations with A. tegalensis population densities in the field (correlation coefficients r: 0.51 and 0.41, respectively; p
Keywords: Biological control, Chilocorus melanophthalmus, predator-prey interaction, Scymnus sp., sugarcane scale insect